مُتخيَّل الاغتراب وسؤال الهُويّة، قراءة في رواية "لامبيدوزا" لمبروك دريدي - حماشي, حسينة (جامعة الوادي - University of Eloued, 2020)
من ارتحالات الرّواية العربية عامة والجزائرية خاصة السّعي إلى التّماشي والتّطورات الفنيّة والجماليّة، فتتناول فيما تتناول قضية "الأنا" ومتعلقاتها، وتطرح إشكاليّة الهُويّة في المتن السّردي، فيتّخِذ المبدِعُ مِن المُتخيَّل بعد تطويعه مطيّة لتجسيد أزمتها؛ بما تحمله من معاني الانتماء كمعادل موضوعي لكينونة الإنسان المشحون، والذي يعيش هجنة ثقافية وإفراغا بسبب ظاهرة الاغتراب، وما ينجر عنها من استلاب هويّاتي يهدّد وجوده، وصراع نفسي محموم مع الأنا الهاربة من إكراهات الواقع الرّاهن، والمنشطِرة عن أصلها، لتبوح بتحدّي مواجهة الذّات والتّمرد عليها بسد تلك الهوّة والعودة، أو تحقيق ولادة جديدة بعيدا عنها، وقد استوعب الرّوائي مبروك دريدي هذا الصّراع سرديا في روايته "لامبيدوزا" The Arabic novel witnesses ongoing technical aesthetic developments, as it tends to deal with the issue of “ego” and its belongings. Algerian authors become increasingly concerned with the identity problematic in the narrative text, where they mold the imaginary after in such a way as to deconstruct the “ego” crisis”, affiliation and identity. Their obvious objective is to equate the charged human being who lives a cultural hybridization, emptying, and alienation, which threaten his/her existence and create a frantic psychological conflict with the escaping or the split ego. This conflict can reveal the challenge of confronting oneself and rebilling against it by filling that gap and coming back, or achieving a rebirth far from what first caused it. This paper attempts to show how the novelist Mabrouk Dridi represents this conflict in his novel "Lampedusa"
the Imaginary Of Alienation And The Identity Question In Mabrouk Dridi’s Novel “lampedusa”
مقال
Keywords: مُتخيَّل/ imaginary ; اغتراب/ alienation ; هُويّة/ identity ; رواية/ novel ; مبروك دريدي/ Mabrouk Dridi